2005
DOI: 10.1111/j.1365-2648.2005.03495.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping with a possible breast cancer diagnosis: demographic factors and social support

Abstract: Better coping was linked primarily to education, and secondly to attachment. Unemployment, low level of education and single/divorced/widowed status were related to greater use of cognitive defence. Women who used a defensive hostile style tended to receive poor social support. Nurses need to be aware of the influence of demographic characteristics on social support, coping and defence and to identify poor copers, as these patients are most in need of professional support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
61
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 49 publications
9
61
0
2
Order By: Relevance
“…Our results indicated that patients after breast cancer diagnosis used several coping strategies in agreement with the Lazarus and Folkman's model [29], which showed that breast cancer patients used various coping strategies after diagnosis in response to stress. Previous studies have demonstrated that some common coping strategies used by breast cancer patients were positive cognitive restructuring, wishful thinking, emotional expression, disease acceptance, increased religious practice, family and seeking social support [29][30][31] Our results seem to be consistent with those of other studies, which found coping strategies changed over time [24,31,32]. Another important finding was that wishful thinking was the least commonly used strategy 6 months after the diagnosis.…”
Section: Discussionsupporting
confidence: 88%
“…Our results indicated that patients after breast cancer diagnosis used several coping strategies in agreement with the Lazarus and Folkman's model [29], which showed that breast cancer patients used various coping strategies after diagnosis in response to stress. Previous studies have demonstrated that some common coping strategies used by breast cancer patients were positive cognitive restructuring, wishful thinking, emotional expression, disease acceptance, increased religious practice, family and seeking social support [29][30][31] Our results seem to be consistent with those of other studies, which found coping strategies changed over time [24,31,32]. Another important finding was that wishful thinking was the least commonly used strategy 6 months after the diagnosis.…”
Section: Discussionsupporting
confidence: 88%
“…An analysis of the total social support and sub-dimension scores of the participants according to their education level reveals that there is a statistically significant difference between education level and total scores and social support friends sub-dimension scores. Studies show that receiving education, by increasing social networks such as friendship or work friendship, affects social support positively (Drageset and Lindstrøm, 2005). Findings of the study conducted by Rustoen and Wiklund (2000) correspond to the findings of the present study in that they found cancer patients with low education level had higher hopelessness scores.…”
Section: Discussionsupporting
confidence: 85%
“…Anxiety is mainly related to uncertainty about the diagnosis, side-effects of chemotherapy or radiotherapy treatment, lack of social or personal control, progressive physical deterioration, and thoughts of near death (3). Studies performed have reported different levels of anxiety in patients with various types of cancer (5)(6)(7)(8)(9). Patients who are depressed may also have physical symptoms which are difficult to palliate and which may improve as their depression is appropriately treated (10).…”
Section: Introductionmentioning
confidence: 99%